Phylogenomics of the North American Plecoptera. (20th November 2020) - South, Eric J.; Skinner, Rachel K.; DeWalt, R. Edward; Kondratieff, Boris C.; Johnson, Kevin P.; Davis, Mark A.; Lee, Jonathan J.; Durfee, Richard S.
Abstract: Stoneflies (Insecta: Plecoptera) provide essential ecosystem services and are vital components of aquatic ecological systems worldwide. Despite this importance, a well‐supported and fully‐resolved phylogeny of the order has remained elusive for over a century. Using transcriptome data from 94 species, we performed maximum likelihood and multispecies coalescent analyses with 1400 orthologous genes. This taxon sample includes representatives of all families, subfamilies and tribes of the North American fauna, providing the most complete molecular phylogenetic study of the North American Plecoptera to date. Analyses recovered high support for the resolution of previously unresolved or contested relationships and the elucidation of a few novel relationships among historically accepted clades. Results included recovering (i) Perlidae as the earliest diverging family of Perloidea, (ii) the clade Nemouridae + Capniidae instead of the traditionally recognized Leuctridae + Capniidae, (iii) Peltoperlidae as sister to four Systellognatha families and (iv) non‐monophyly of Chloroperlidae due to placement of the genus Kathroperla Banks. The position of Taeniopterygidae and Leuctridae remain inconclusive, as the placement of these taxa was not consistent between analyses of different data types nor was strong support for their relationships to other stoneflies recovered in a four‐cluster likelihood analysis. However, our results for the North American taxa establish a robust foundation for future phylogenetic studies of the Plecoptera world fauna. Abstract : Using transcriptome data from 94 species, we provide the most complete molecular phylogenetic study of the North American Plecoptera to date. Results included recovering (i) Perlidae as the earliest diverging Perloidea family, (ii) the clade Nemouridae + Capniidae, (iii) Peltoperlidae as sister to four Systellognatha families and (iv) non‐monophyly of Chloroperlidae. The phylogenetic position of Taeniopterygidae and Leuctridae remain inconclusive.